EKSTRAKSI TANPA SOLUSI: PENOLAKAN BURUH TERHADAP PEMOTONGAN GAJI PADA PROGRAM TABUNGAN PERUMAHAN RAKYAT (TAPERA) - Laila Annisa Fitri (Journal of Politic and Government Studies, 2026)
The People's Housing Savings Program (Tapera) is a government policy designed to help citizens obtain adequate housing through a mandatory savings scheme. This policy requires workers to allocate a portion of their salary as Tapera contributions. However, its implementation has generated various forms of resistance from workers in several regions, including Semarang City. This study aims to analyze the factors underlying workers’ resistance to the Tapera salary deduction policy and to examine the forms of mobilization carried out by labor organizations. This research employs a qualitative method with a case study approach. The analysis uses Ted Robert Gurr’s theory of relative deprivation to explain the gap between workers’ expectations of welfare improvement and their actual economic capabilities. The findings reveal that workers’ resistance emerged due to the mismatch between workers’ expectations for improved welfare and government policies that increased their economic burden through mandatory salary deductions. Furthermore, workers perceive the Tapera program as failing to provide a clear solution to their housing needs. The resistance developed through two primary channels: open protests through demonstrations and mass mobilization, and closed channels through advocacy and policy lobbying. The study concludes that public policies that do not consider the socio-economic conditions of their target groups may trigger social resistance and potentially reduce governmental legitimacy.